2004
DOI: 10.1023/b:aseb.0000026618.16408.e0
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Health: A Useful Public Health Paradigm or a Moral Imperative?

Abstract: The past decade has shown an increasing use of the concept of sexual health. This upsurge is especially noticeable not only in the field of health education and promotion but also in academic sources. The concept is typically used self-evidently and with widely diverse connotations. The definition and understanding of sexual health are still evolving and pose various critical questions. For instance, the term sexual health may imply various risks, including a one-sided health perspective on sexuality and a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
34
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 34 publications
0
34
0
1
Order By: Relevance
“…Different approaches that have been evaluated to address these issues will also be discussed. Key Words: sexuality; contraception; sterilization; sexually transmitted disease; hygiene management; pregnancy S exual health is influenced by a variety of political and social events and is broader than the absence of disease [Edwards and Coleman, 2004], encompassing both mental and physical aspects of human functioning that are important to overall well being [Sandfort and Ehrhardt, 2004]. The concept of sexual health in persons with intellectual disabilities (ID) is an extremely sensitive subject, and while advances have been made in employment, housing, and other aspects of community integration, the sexual needs of these individuals have been relatively ignored or strictly controlled by caregivers and service agencies [Bambara and Brantlinger, 2002; Hinsburger and Tough, 2002].…”
mentioning
confidence: 99%
“…Different approaches that have been evaluated to address these issues will also be discussed. Key Words: sexuality; contraception; sterilization; sexually transmitted disease; hygiene management; pregnancy S exual health is influenced by a variety of political and social events and is broader than the absence of disease [Edwards and Coleman, 2004], encompassing both mental and physical aspects of human functioning that are important to overall well being [Sandfort and Ehrhardt, 2004]. The concept of sexual health in persons with intellectual disabilities (ID) is an extremely sensitive subject, and while advances have been made in employment, housing, and other aspects of community integration, the sexual needs of these individuals have been relatively ignored or strictly controlled by caregivers and service agencies [Bambara and Brantlinger, 2002; Hinsburger and Tough, 2002].…”
mentioning
confidence: 99%
“…However, the prevalence of sexual dysfunction is high in Iran and in the world; various studies indicated the prevalence of 20% to 40% for sexual dysfunction in Iran and 25% to 65% in Europe and the United States (18)(19)(20)(21). Nonetheless, the types of sexual dysfunction caused by lower extremity trauma have not been well-defined.…”
Section: Introductionmentioning
confidence: 99%
“…Semantically, "sexual health," once the province only of sexually transmitted infections (STIs), unintended pregnancies, and other undesirable consequences, has grown to encompass indicators of sexual well-being. 1 Adult is the pinnacle of all stages of human growth and development. More attention has been placed on sexual health by the World Health Organization (WHO) by declaring that; "There exist fundamental rights for the individual, including freedom from organic disorders, diseases and deficiencies that interfere with sexual and reproductive function".…”
Section: Introductionmentioning
confidence: 99%